Women’s Language Features in Billie Eilish and Olivia Rodrigo Interviews - Adelia Yuliana Bakari; Usman Pakaya; Jefriyanto Saud (Universitas Islam Negeri Palopo, 2026)
This study examines how women's language features are used in press interviews conducted with Billie Eilish and Olivia Rodrigo. This research draws on Lakoff's (1975) theory, which outlines ten characteristics of women's language and seeks to identify the linguistic features that emerge from the spontaneous speech of both artists. The study uses a descriptive qualitative approach by studying statements from six press line interview videos retrieved from YouTube. It then prioritized the data with lexical hedges or fillers, tag questions, rising intonation, empty adjectives, precise color term, intensifiers, hypercorrect grammar, superpolite form, avoidance of strong words and emphatic stress using Lakoff classification criteria. The findings reveal that several features frequently appear in the interviews, particularly lexical hedges or fillers, intensifiers, empty adjectives, and emphatic stress. These features reflect the spontaneous and natural speaking style of the artists in media settings. The study does not aim to compare the two singers or evaluate which one uses more women’s language features; rather, it describes how each artist demonstrates linguistic patterns associated with women’s language in unscripted public interactions. The results contribute to sociolinguistic discussions on language and gender, particularly in contemporary media discourse involving young female celebrities.